2015
DOI: 10.1016/j.ijscr.2015.06.032
|View full text |Cite
|
Sign up to set email alerts
|

10 Levels thoracic no-intrumented laminectomy for huge spontaneous spinal subdural hematoma removal. Report of the first case and literature review

Abstract: HighlightsIn this article, reporting on the case of a huge 10 levels spontaneous spinal subdural hematoma treated with decompressive thoracic no-instrumented laminectomy in a 45-year-old woman with good neurological recovery, we would like to underline the importance of a timely surgical decompression as the mainstay option in the management of strongly symptomatic spontaneous idiopathic acute spinal subdural hematomas.To our knowledge, 10 levels thoracic laminectomy for a SSDH removal have never been describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Although our patient denied intravenous drug use, a history of drug abuse cannot be excluded, especially considering the positive urine drug test for amphetamines. Two cases of spontaneous sSDH in association with amphetamines have previously been reported [ 31 , 40 ]. Amphetamine use has been associated with both intracranial hemorrhage and cerebral vasculitis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our patient denied intravenous drug use, a history of drug abuse cannot be excluded, especially considering the positive urine drug test for amphetamines. Two cases of spontaneous sSDH in association with amphetamines have previously been reported [ 31 , 40 ]. Amphetamine use has been associated with both intracranial hemorrhage and cerebral vasculitis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature has shown that contrast-enhanced time-resolved MR angiography was 88% sensitive, 90% specific and had a positive predictive value of 88%, and negative predictive value of 90% for detection of spinal dural arterial venous fistulas [ 50 ]. Digital subtraction spinal angiography is considered the gold standard for identifying vascular abnormalities and is frequently used in evaluation of the bleeding source [ 40 ]. However, Braun et al suggest performing spinal angiography when clinical suspicion of vascular malformation exists based on MRI findings [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with major deficits or with clinical and radiological aggravation (CT, MRI) should be treated urgently, even after long compression of the spinal cord. In such cases early decompression by laminectomy with evacuation of the hematoma is considered to be the best treatment [23].…”
Section: Discussionmentioning
confidence: 99%
“…Acute surgical decompression and discontinuation of anticoagulants is the standard of care in any patient on anticoagulants who is suspected of having a subdural hematoma [1215]. Studies involving subdural and epidural hematomas of various etiologies suggest optimum results when surgical decompression occurs within 24 hours from the onset of symptoms [13, 16]. Large multilevel laminectomies for spinal hematoma management have shown to be safe and effective based on the limited literature available.…”
Section: Discussionmentioning
confidence: 99%